2018
DOI: 10.4049/jimmunol.1701681
|View full text |Cite
|
Sign up to set email alerts
|

MTOR Suppresses Cigarette Smoke–Induced Epithelial Cell Death and Airway Inflammation in Chronic Obstructive Pulmonary Disease

Abstract: Airway epithelial cell death and inflammation are pathological features of chronic obstructive pulmonary disease (COPD). Mechanistic target of rapamycin (MTOR) is involved in inflammation and multiple cellular processes, e.g., autophagy and apoptosis, but little is known about its function in COPD pathogenesis. In this article, we illustrate how MTOR regulates cigarette smoke (CS)-induced cell death, airway inflammation, and emphysema. Expression of MTOR was significantly decreased and its suppressive signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 45 publications
2
68
0
Order By: Relevance
“…Mitani et al (24) 2016 Experimental Restored corticosteroid sensitivity by rapamycin. Wang et al (25) 2018 Experimental Suppression of cigarette smoke-induced cell death, airway inflammation and emphysema by mTOR, likely through modulation of autophagy, apoptosis and necroptosis. Duran et al (26) 2014 Clinical Current knowledge of drug-induced pneumonitis (mechanism, clinical impact and management) in cancer patients treated with mTOR inhibitors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitani et al (24) 2016 Experimental Restored corticosteroid sensitivity by rapamycin. Wang et al (25) 2018 Experimental Suppression of cigarette smoke-induced cell death, airway inflammation and emphysema by mTOR, likely through modulation of autophagy, apoptosis and necroptosis. Duran et al (26) 2014 Clinical Current knowledge of drug-induced pneumonitis (mechanism, clinical impact and management) in cancer patients treated with mTOR inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a very elegant and recent study on isolated airway epithelium of human COPD and in mouse lung chronically exposed to cigarette smoke shows that activation of mTOR and/or inhibition of autophagy may be a new mechanism of cigarette smoke-induced COPD (25).…”
Section: Mtor Targeting In Lung Diseasesmentioning
confidence: 99%
“…By examining the process of apoptosis and trans-differentiation, we provide insights into the molecular basis of tissue remodeling in chronic lung disease. Importantly, the roles of autophagy and the use of Rapamycin have been considered in the context of COPD and Asthma, were tested in various models, but with variable effects (Kennedy and Pennypacker, 2016;Lam et al, 2013;Mitani et al, 2016;Mushaben et al, 2011;Wang et al, 2018). Cell type-specific effects of Rapamycin in the airways were discussed, but without reaching a consensus.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to cigarette smoke has been shown to increase AMPK activation in the lungs in a CSC concentration-dependent and timedependent manner [54]. A recent study also showed that the activation of mTOR suppressed airway inflammation and emphysema induced by cigarette smoke via the inhibition of autophagy and cell death [55]. Furlong et al showed that in the mouse ovary, cigarette smoke exposure activated autophagy by upregulating the AMPK/mTOR pathway [42].…”
Section: Discussionmentioning
confidence: 99%